2021
DOI: 10.1080/21870764.2021.1891662
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature synthesis and phase transformation of lithium phosphate Li3PO4as solid electrolyte

Abstract: We successfully prepared single-phase sample of the low-temperature β-type form of lithium phosphate Li 3 PO 4 by a stoichiometric mixing of LiOH solution and NH 4 H 2 PO 4 powder at room temperature without heating. The orthorhombic lattice parameters with the space group of Pmn2 1 for β-Li 3 PO 4 were refined to be a = 6.1281(6) Å, b = 5.2674(5) Å, c = 4.8923(2) Å, and V = 157.92(2) Å 3. We also prepared the single-phase sample of high-temperature γ-Li 3 PO 4 by heating the β-Li 3 PO 4 at 650°C. The orthorho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…The observed peak positions coincided with the cubic crystal structure with the F 4̅3 m space group. This confirmed the successful formation of Li-argyrodite type solid electrolyte. In addition, Li 3 PO 4 impurity peaks were observed at 2θ = 22.0°, 22.9°, 24.5°; Li 2 S and LiCl impurity peaks were observed at 26.8° and 49.9°, respectively . Usually, impurity peaks of Li 3 PO 4 , Li 2 S, and LiCl are observed during the preparation of argyrodite solid electrolyte by solution synthesis.…”
Section: Resultssupporting
confidence: 54%
“…The observed peak positions coincided with the cubic crystal structure with the F 4̅3 m space group. This confirmed the successful formation of Li-argyrodite type solid electrolyte. In addition, Li 3 PO 4 impurity peaks were observed at 2θ = 22.0°, 22.9°, 24.5°; Li 2 S and LiCl impurity peaks were observed at 26.8° and 49.9°, respectively . Usually, impurity peaks of Li 3 PO 4 , Li 2 S, and LiCl are observed during the preparation of argyrodite solid electrolyte by solution synthesis.…”
Section: Resultssupporting
confidence: 54%
“…For Li 3 PO 4 single phase sample was investigated and reported by Norikazu et al ( 2021) that particles of size 20-30 nm suitable for the fabrication of dense solid electrolyte in all-solid-state lithium battery applications (28) . Our present glass system BPZL6 and BPZL7 are containing the crystallite size of 21-25 nm is comparable to Li 3 PO 4 nano-crystallite phase.…”
Section: Conductivitymentioning
confidence: 99%
“…Indeed, γ-Li 3 PO 4 is known to have higher Li-ion conduction than β-Li 3 PO 4 . Since it had been reported that β-Li 3 PO 4 transformed to γ-Li 3 PO 4 around 723 K, 33 we attempted to convert experimentally obtained β-Li 3 PO 4 -type Li 2.75 [B 0.625 P 0.125 S 0.25 ]O 3.375 to γ-Li 3 PO 4 -type structure by heat treatment, but it was not successful. It is also possible that the bulk ionic conductivity is higher and the grain boundary lowers the total conductivity.…”
Section: R Y S T a L S T R U C T U R E O F H P -S Y N T H E S I Z E D Limentioning
confidence: 99%